Replication in experimental economics - Deck, Cary A.; Fatas, Enrique; Rosenblat, Tanya, 1971- (Bingley, U.K. : Emerald, 2015)
Replication in experimental economics' highlights the importance of replicating previous economic experiments for understanding the robustness and generalizability of behavior. Replication enables experimental findings to be subjected to rigorous scrutiny. Despite this obvious advantage, direct replication remains relatively scant in economics. One possible explanation for this situation is that publication outlets favor novel work over tests of robustness. This volume of Research in experimental economics raises awareness of the need for replication by being the first collection of papers specifically dedicated to the replication of previously published work. The chapters, by leading researchers in the field, explore the robustness of topics from the effects of subsidizing charitable giving to people's ability to backwards induct and from the impact of social history on trust to the role of isolation on valuation. Readers will gain a better understanding of the role that replication plays in scientific discovery as well as valuable insights into the robustness of previously reported findings.
Four classic public goods experiments : a replication study / Catherine Eckel, Haley Harwell, Jose<U+0301> Castillo -- The impact of social information on the voluntary provision of public goods : a replication study / James J. Murphy ... [et al.] -- On replication and perturbation of the McKelvey and Palfrey centipede game experiment / James C. Cox, Duncan James -- The impact of financial histories on individuals and societies : a replication of and extension of Berg et al. (1995) / Xu Jiang, Radhika Lunawat, Brian Shapiro -- Revisiting the effect of voter isolation / Alexander G. James, Jason F. Shogren -- Non-verbal feedback, strategic signaling, and non-monetary sanctioning : new experimental evidence from a public goods game / Adam Zylbersztejn -- When and why matches are more effective subsidies than rebates / Rene<U+0301> Bekkers -- How to make experimental economics research more reproducible : lessons from other disciplines and a new proposal / Zacharias Maniadis, Fabio Tufano, John A. List.
Print version record
Keywords: Business & Economics -- Econometrics; Econometrics; Experimental economics; Replication (Experimental design)